Generative and transformational techniques in software engineering III International Summer School, GTTSE 2009, Braga, Portugal, July 6-11, 2009. Revised Papers - Fernandes, João M.; Lämmel,Ralf; Visser, Joost; Saraiva, João (Springer, 2011)
This tutorial book presents revised and extended lecture notes for a selection of the contributions presented at the International Summer School on Generative and Transformational Techniques in Software Engineering (GTTSE 2009), which was held in Braga, Portugal, in July 2009. The 16 articles comprise 7 long tutorials, 6 short tutorials and 3 participants contributions; they shed light on the generation and transformation of programs, data, models, metamodels, documentation, and entire software systems. The topics covered include software reverse and re-engineering, model driven engineering, automated software engineering, generic language technology, and software language engineering.